Dots Wear: produce and sell lumi shirt / Syed Ikmal Hadi Syed Shaharuddin [et al.] - Syed Shaharuddin, Syed Ikmal Hadi; Wan Azlan, Wan Muhammad Arfan; Mohd Asri, Wan Muhammad Asyra; Mohd Nasir, Muhammad Faris; Mohd Noor, Muhammad Amiruddin; Naim, Muhanmad Iqba; Abdul Razak, Muhammad nazrin (2015)
Dots wear produce and sell lumi shirt and as we know, some cyclist tend to cycle in the dark thus, that is when our product will become of use to them.